СЛОВНИК МОВИ ПИСЬМЕННИКА І ПРОБЛЕМИ ДОСЛІДЖЕННЯ ЛЕКСИЧНОЇ ІДІОСИСТЕМИ ХУДОЖНЬОГО ТВОРУ - Chakal (Makar), Inesa (Аксіома, 2016)
The article analyzes the importance of writers’ language vocabularies compiling not only for researching the lexical idiosystem of their works, but also for investigating the authors’ creative work, for studying the relevant stage of language history. Linguistic means in a fiction text is not accidental, casual complete set of various elements. They interact not only with the extralinguistic factors, but also between themselves within certain levels and in inter-level way. Concordance-dictionaries and index-dictionaries are closely related to the concept ‘writer’s idiostyle’. They make it possible to form in detail the author's idiolect and identify lexical-semantic and grammatical-stylistic dominants of fiction language which are characterizing his idiostyle. Lexical structure of a literary text depends on several factors: the subject of the work, the individual style of the writer, the peculiarity of his world outlook, linguistic consciousness and writing manner (creating of a conceptual world view, special conceptual sphere, system of speech figures etc.). Among the main types of lexical microsystems most suitable for the researching of writer’s language vocabulary we suppose the lexical-semantic groups which may cover most of his lexical idiosystem. Partition of lexemes on lexical-semantic groups according to the structural-semantic and onomasiological characteristics of words and quantitative index of their functioning in the text is very important for describing of author’s idiostyle. Lexemes system analysis of same epoch works, following writer’s language vocabularies, partition of lexical-grammatical classes and lexical-semantic groups, identifying of verbal set of actual lexicon dominants can prove the uniqueness of each writer idiostyle in particular. Проаналізовано важливість укладання словників мови письменників не лише для дослідження лексичної ідіосистеми їхніх творів, але й для вивчення творчості самих авторів, дослідження відповідного етапу історії певної літературної мови. Системний аналіз лексики творів однієї епохи за словниками мови письменників, виокремлення ЛГК та ЛСГ, виявлення домінант вербальної сітки актуалізованого лексикону може засвідчити неповторність ідіостилю кожного письменника зокрема.
Keywords: словник мови письменника; лексична ідіосистема; ідіостиль; лексико-семантична група; парадигматичні відношення; актуалізований лексикон; writer’s language vocabulary; lexical idiosystem; idiostyle; lexical- semantic group; paradigmatic relations; actual lexicon